Estimation And Analysis Of The Cucumber Production Function In Greenhouse In Erbil Governorate During 2010 - Dawood, Saber P.; Mohammad, Salam H. (Humanities Journal of University of Zakho, 2018)
Vegetable crops, including cucumber, contribute to secure an important part of human food needs, as well as contribute to local investment, employment and generate income, consequently, in agricultural growth. Moreover, estimating cucumber production function provides producers by quantitative indicators which assist them in making sound production decisions and increase their profits, thus motivating them to continue in the production process , as well as enhancing it. The problem lies in the lack of domestic supply to meet the growing demand due to seasonal production, while demand for the crop throughout the year. Moreover, inefficient use of inputs, especially for greenhouse, reduces producer’s profits, thus reducing the motivations to continue in the production process. The study aimed at deriving some economic indicators that derived from estimated production function of cucumber, by using (OLS) method, in order to determine optimal level of inputs. To achieve this goal the data has been collected via questionnaire from 124 greenhouses of cucumber farms in Erbil governorate in year 2010, which constitute %47.5 of theses farms. The results showed that output elasticity of labor, capital and acreage amounted to (%11) , (%17) and (%33). respectively. Finally, the study reached to a number of conclusions and proposals that serve both the development of cucumber production and future related studies.